Struktur Komunitas Mesofauna Tanah dan Kapasitas Infiltrasi Air setelah diberi Perlakuan Biostarter Pengurai Bahan Organik - Andriani, Latifah Fitria; Rahadian, Rully; Hadi, Mochamad (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2013)
Research about the biostarter application on the biopori concept through parameter of soil mesofauna community structure and water infiltration capacity was aimed to investigate the effect of biostarter product on soil mesofauna community structure and water infiltration rate at Lubang Resapan Biopori (LRB) aged 30 days and 50 days, also the correlation between mesofauna community structure and soil infiltration capacity. This study uses a single factor completely randomized design, which has 5 treatments including control, EM4, Bioklin, Mig Dec, and Orgadec. The results showed that the addition of biostarter affects soil mesofauna community structure, particularly positive effect on the abundance of Oribatida and Mesostigmata. Products Orgadec was able to increase faster the abundance of mesofauna both at the age of LRB 30 days and 50 days, whereas Mig Dec and EM4 starting to show its influence on the LRB after 50 days. Infiltration rate LRB age of 30 days showed a significant difference in treatment of Orgadec only, whereas at the age of 50 days, the significant difference is indicated in the treatment EM4â€‹â€‹, Mig Dec and Orgadec. Based on the Spearman correlation test, the total number of individuals and number of Oribatida. Both showed significant positive correlation with the infiltration rate. Â Keywords: biostarter, community structure, soil mesofauna, infiltration rate, LR